Criminal Aspects For Legal Processing On Persons Abuse Of Illegible Drugs - Yanto Mulyanto P; Achmad Sulchan (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to find out, examine and analyze the implications of the criminal aspect in the implementation of the Health Law on perpetrators of drug abuse. This research uses normative juridical method. Based on the research, it can be concluded that in the application of the criminal act of distributing and abusing pharmaceutical preparations without a distribution permit as regulated in Article 197 of Act No. 36 of 2009 concerning Health, the formulation contained in this article is anyone who intentionally produces or circulate pharmaceutical preparations and/or medical devices that do not have a distribution permit as referred to in Article 106 paragraph (1), namely pharmaceutical preparations and medical devices can only be circulated after obtaining a distribution permit. Accountability in criminal law is carried out on the basis of error and some is carried out without having to prove the existence of the error (strict liability Errors can be divided into two types, namely intentional and negligence. Therefore, it is necessary to form a general health policy that can be implemented by all parties and at the same time can answer the challenges of the era of globalization and with the increasing complexity of health problems in a new Health Law to replace Law Number 23 of 1992 concerning Health with Law No. Law Number 36 Year 2009 concerning Health.